Collaboration with Hans‐Beat Bürgi: crystallography at Bern and Lausanne. Issue 3 (20th April 2022) - Schwarzenbach, Dieter
Abstract : Memories of the scientific collaboration over several decades of the crystallographers at the Universities of Bern and Lausanne are shared. Abstract : A personal recollection of scientific developments by Hans‐Beat Bürgi and fellow crystallographers in Switzerland is given.